Effects of socioeconomic status on risk of ischemic stroke: a case-control study in the Guangzhou population - Siping Wang; Binyan Shen; Meiting Wu; Ciyu Chen; Juan Wang (BMC, 2019)
Abstract Background The association between socioeconomic status (SES) and stroke risk remains controversial around the world. It is not clear that the effect of SES on stroke in China due to the lack of relevant research. We aimed to assess the association between SES and risks of first-ever ischemic stroke in Guangzhou, China. Methods Cases were recruited from neurology department in the First Affiliated Hospital of Guangdong Pharmaceutical University during September 2016-October 2017. Age- and sex-matched controls were derived from surgical departments, over the same period. SES was assessed based on education, occupation, and income. Education was divided into ≤6 years, 6-9 years, 10-12 years, and > 12 years. Family monthly income per capita was categorized into ≤¥1000, ¥1001-3000, ¥3001-5000, and > ¥5001. Occupation was stratified into manual, non-manual, no job, and retired. A multivariate logistic regression model was used to determine the association between SES and risk of ischemic stroke. Results In total, 347 ischemic stroke patients and 347 controls were recruited, with mean ages of 60.54 ± 13.13 and 60.56 ± 13.07 years, respectively. After adjusting for confounding factors, odds ratio (OR) for 6-9 years of education was 2.63 (95% confidence interval [CI] 1.45-4.75); > 12 years, 2.18 (1.25-3.82) compared with those for < 6 years of education. ORs for the second lowest, third lowest, and highest incomes were 1.96 (1.21-3.15), 4.16 (2.39-7.22), and 2.83(1.25-6.39), respectively, compared with those for the lowest income. ORs for manual workers and non-manual workers were 1.95 (1.23-3.07) and 1.87 (1.05-3.33), compared with individuals without jobs. Conclusions Higher SES is positively related with risks of ischemic stroke, explained by cardiovascular diseases and unhealthy lifestyles in Guangzhou, China. Thus, effective strategies such as extensive health education, promoting a healthy lifestyle, screening for risk factors to prevent stroke should be implemented to reduce ischemic stroke incidences among the high SES group.